Penguatan Karakter Anak Usia Dini melalui Pembelajaran Proyek Kontekstual di PAUD Makassar - Junaedah; Abdul Majid (Lembaga Yasin AlSys, 2026)
Character education in early childhood education has become a policy priority, but evidence regarding the effectiveness of contextual project-based learning that integrates observable character habituation in urban early childhood education settings in Indonesia remains limited. This study aimed to model the effectiveness of an eight-week contextual project-based learning program in strengthening discipline, responsibility, cooperation, empathy, and honesty among children aged 5–6 years in Makassar City. The study employed a simulated quasi-experimental design with an analytical dataset comprising 120 simulated child records from six anonymized early childhood education centers, consisting of 60 children in the experimental group and 60 children in the comparison group. The data were represented using a 25-item structured observation instrument and analyzed using descriptive statistics, paired comparisons, analysis of covariance controlling for pretest scores, heteroskedasticity-consistent standard errors, effect sizes, and sensitivity analysis. The simulation results showed that the mean score of the experimental group increased from M = 66.83 (SD = 6.91) to M = 79.64 (SD = 7.38), whereas the comparison group increased from M = 66.58 (SD = 6.54) to M = 73.70 (SD = 7.61). After controlling for pretest scores, the between-group difference was estimated at 5.71 points (95% CI = 4.25–7.16; p < 0.001), with a large partial effect size. Cooperation and discipline showed the most consistent improvement, whereas honesty demonstrated the smallest effect. These simulated findings indicate that contextual project-based learning has the potential to provide children with repeated, meaningful, and social experiences in practicing character values through actions rather than solely through verbal instruction. Theoretically, this study integrates social-emotional learning, self-regulation, guided play, and the character strengths perspective, while practically, the results can serve as a basis for teachers’ instructional planning, observational assessment, and the development of locally contextualized projects. However, because all research data were simulated, these findings require verification through empirical studies involving actual participants, preregistered protocols, longer follow-up periods, and multilevel analysis.